PROBLEMATIKA YANG DIHADAPI GURU DI SEKOLAH DALAM KONTEKS SUPERVISI PENDIDIKAN - Muhamad Sidiq, Sultan; Muslimah, Muslimah (Berajah Journal, 2024)
In order to enhance the quality of education, government educational institutions provide supervision and guidance, which is defined as the effort of school officials in leading teachers and other officers in improving teaching. This encompasses stimulating, selecting, and fostering the growth and development of teachers, as well as revising educational goals, teaching materials and methods, and evaluating teaching. The scope of educational supervision is divided into two aspects: the human aspect and the activity aspect. The human aspect of educational supervision concerns the attitudes of all those involved in educational institutions, including teachers, administrators, and other staff. It encompasses issues such as duty, work discipline, work morale, honesty, and obedience to organisational rules. The aspects of activity, as defined by Suwoto, include how to work (how to teach), methods of approaching students, work efficiency, and work results. Three operational elements that must be considered in this aspect are: (1) educational techniques, (2) administrative techniques and (3) coordination and cooperation. However, each aspect of the scope has its own set of realities, problems and hopes to be realised in order to improve the quality of educational institutions.